2021
DOI: 10.1242/jeb.222083
|View full text |Cite
|
Sign up to set email alerts
|

Cool your jets: biological jet propulsion in marine invertebrates

Abstract: Pulsatile jet propulsion is a common swimming mode used by a diverse array of aquatic taxa from chordates to cnidarians. This mode of locomotion has interested both biologists and engineers for over a century. A central issue to understanding the important features of jet-propelling animals is to determine how the animal interacts with the surrounding fluid. Much of our knowledge of aquatic jet propulsion has come from simple theoretical approximations of both propulsive and resistive forces. Although these mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 128 publications
(228 reference statements)
0
18
1
Order By: Relevance
“…There are few published estimates of efficiency and cost of transport for siphonophores, but our modeled cost of transport for an N. bijuga colony with two nectophores swimming asynchronously, 6.3 J kg −1 m −1 , was similar to the 3 J kg −1 m −1 calculated by Bone and Trueman ( 21 ) for the calycophoran siphonophore Abylopsis tetragona , which has one full-sized and one reduced nectophore. N. bijuga colonies with five or more nectophores were found to have costs of transport less than 3 J kg −1 m −1 when swimming asynchronously, putting them toward the lower end of reported values for jet-propelled swimmers ( 2 ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…There are few published estimates of efficiency and cost of transport for siphonophores, but our modeled cost of transport for an N. bijuga colony with two nectophores swimming asynchronously, 6.3 J kg −1 m −1 , was similar to the 3 J kg −1 m −1 calculated by Bone and Trueman ( 21 ) for the calycophoran siphonophore Abylopsis tetragona , which has one full-sized and one reduced nectophore. N. bijuga colonies with five or more nectophores were found to have costs of transport less than 3 J kg −1 m −1 when swimming asynchronously, putting them toward the lower end of reported values for jet-propelled swimmers ( 2 ).…”
Section: Resultsmentioning
confidence: 87%
“…Pulsed jets are an efficient, convergent solution to swimming propulsion for a broad taxonomic range of marine organisms, including cnidarians, cephalopods, and pelagic tunicates ( 1 , 2 ). Swimming through the use of multiple pulsed jets is much less common.…”
mentioning
confidence: 99%
“…Their ability to filter and concentrate small, suspended particles comes from their unique hydrodynamic pumping strategy. Suggestions for bioinspired underwater vehicle and robotic design have focused on the kinematics and hydrodynamics of swimming in fish and invertebrates [13][14][15]55,[69][70][71]. The range of mechanisms that suspension feeding metazoans employ to separate particles from a fluid suspension is another fertile ground for biomimetic applications [28].…”
Section: Discussionmentioning
confidence: 99%
“…This feature suggested that their different locomotion strategies, such as crawling or jetmotion, may correlate with their different metabolic strategies. Despite the fact that jet propulsion is not an efficient locomotion pattern that requires too much energy from aerobic respiration, this pattern is capable of rapid acceleration and locomotion (O'Dor and Webber, 1991;Gemmell et al, 2021). Octopuses, on the other hand, are considered to be jet-propulsion abandonment members (Wells, 1990;Huffard, 2006).…”
Section: Discussionmentioning
confidence: 99%